Chironomidae com recurso alimentar para Leporinus amblyrhynchus (Teleostei: Characiformes) e Pimelodus maculatus (Teleostei: Siluriformes) em um reservatório brasileiro (Lundiana: International Journal of Biodiversity, 2002)
The objective of this study was to demonstrate the importance of chironomid (Diptera, Insecta) larvae as food resource for Leporinus amblyrhynchus Garavello & Britski, 1987 (Anostomidae, Characiformes) and Pimelodus maculatus Lacépède 1803 (Pimelodidae, Siluriformes) and to call attention for the importance of the trophic relation between fish and chironomids assemblages in Miranda reservoir in Araguari River (Minas Gerais State, Brazil), focusing on the influence of the dam on the structure and taxonomic composition of chironomid assemblage. A total of 318 stomach contents of L. amblyrhynchus and P. maculatus were checked of which 108 had chironomid larvae. The number of chironomid larvae observed in stomach contents was higher for L. amblyrhynchus (86.3%) than for P. maculatus (52.7%). The recorded taxonomic richness of chironomid larvae in the stomach contents, suggest that these two fish species invest considerable time and energy feeding on chironomid larvae, thus consisting an important food resource. The recorded data constitute important additional information on the biology of the two studied fish species.